Biliverdin Reductase B Dynamics Are Coupled to Coenzyme Binding. Issue 18 (14th September 2018) - Paukovich, Natasia; Xue, Mengjun; Elder, James R.; Redzic, Jasmina S.; Blue, Ashley; Pike, Hamish; Miller, Brian G.; Pitts, Todd M.; Pollock, David D.; Hansen, Kirk; D'Alessandro, Angelo; Eisenmesser, Elan Zohar
Abstract: Biliverdin reductase B (BLVRB) is a newly identified cellular redox regulator that catalyzes the NADPH-dependent reduction of multiple substrates. Through mass spectrometry analysis, we identified high levels of BLVRB in mature red blood cells, highlighting the importance of BLVRB in redox regulation. The BLVRB conformational changes that occur during conezyme/substrate binding and the role of dynamics in BLVRB function, however, remain unknown. Through a combination of NMR, kinetics, and isothermal titration calorimetry studies, we determined that BLVRB binds its coenzyme 500-fold more tightly than its substrate. While the active site of apo BLVRB is highly dynamic on multiple timescales, active site dynamics are largely quenched within holo BLVRB, in which dynamics are redistributed to other regions of the enzyme. We show that a single point mutation of Arg78➔Ala leads to both an increase in active site micro-millisecond motions and an increase in the microscopic rate constants of coenzyme binding. This demonstrates that altering BLVRB active site dynamics can directly cause a change in functional characteristics. Our studies thus address the solution behavior of apo and holo BLVRB and identify a role of enzyme dynamics in coenzyme binding. Graphical abstract: Unlabelled Image Highlights: Biliverdin reductase B (BLVRB) is present in red blood cells. The BLVRB active site is highly dynamic in the apo form. Active site dynamics are quenched within holo BLVRB. Mutation of the BLVRB active site residues Arg78 increases both the rates of chemical exchange within the active site and the on/off rates of the coenzyme.